An empirical study of the relationship between accounting conservatism and executive compensation-performance sensitivity. Issue 1 (4th March 2019) - Zhang, Xi; Gao, Simon; Zeng, Yi
Abstract : Purpose: The purpose of this paper is to study the relationship between accounting conservatism and executive compensation-performance sensitivity with a view to identify the influence of accounting conservatism on the efficiency of executive compensation contracts. Design/methodology/approach: This study uses multiple regression models based on the approach ofIyengar and Zampelli (2010), Clarkson et al. (2011) andHuang and Kisgen (2013) with the data from all of China's listed non-financial firms over the period of 10 years to test the relationship between accounting conservatism and the sensitivity of executive compensation-performance. Findings: This study finds a positive association between executive compensation and accounting-based measure of performance. More importantly, it reveals that conservatism has a positive relation with the executive compensation-performance sensitivity after controlling for a number of firm-specific factors and control variables. This study shows that the sensitivity of executive compensation to firm performance is higher for firms with higher accounting conservatism. Originality/value: This is one of the few studies to examine the relationship between accounting conservatism and executive compensation-performance sensitivity. It provides supportive evidence to the argument that accounting conservatism, being an efficient governance mechanism, can help mitigate information risk and moral risk for agency problems.